Symptom burden profile in myelofibrosis patients with thrombocytopenia: Lessons and unmet needs. (December 2017) - Scotch, Allison H.; Kosiorek, Heidi; Scherber, Robyn; Dueck, Amylou C.; Slot, Stefanie; Zweegman, Sonja; Boekhorst, Peter A.W.te; Commandeur, Suzan; Schouten, Harry; Sackmann, Federico; Fuentes, Ana Kerguelen; Hernández-Maraver, Dolores; et al.
Highlights: Symptom burden in myelofibrosis patients was assessed via the MPN-SAF and MPN-10. Thrombocytopenic patients had higher individual and total symptom scores. Severely thrombocytopenic patients had different clinical features but similar QOL. MF patients with thrombocytopenia may benefit from therapy to decrease symptoms. Abstract: Myelofibrosis is a myeloproliferative neoplasm associated with progressive cytopenias and high symptom burden. MF patients with thrombocytopenia have poor prognosis but the presence of thrombocytopenia frequently precludes the use of JAK2 inhibitors. In this study, we assessed quality of life and symptom burden in 418 MF patients with (n = 89) and without (n = 329) thrombocytopenia using prospective data from the MPN-QOL study group database, including the Myeloproliferative Neoplasm Symptom Assessment Form (MPN-SAF) and Total Symptom Score (MPN10). Thrombocytopenia, defined as platelet count <100 × 10 9 /L (moderate 51–100 × 10 9 /L; severe ≤50 × 10 9 /L), was associated with anemia (76% vs. 45%, p <  0.001), leukopenia (29% vs. 11%, p <  0.001), and need for red blood cell transfusion (35% vs. 19%, p  = 0.002). Thrombocytopenic patients had more fatigue, early satiety, inactivity, dizziness, sad mood, cough, night sweats, itching, fever, and weight loss; total symptom scores were also higher (33 vs. 24, p <  0.001). Patients with severe thrombocytopenia were more likely to have anemia (86% vs. 67%, p  = 0.04), leukopenia (40% vs. 20%, p  = 0.04), and transfusion requirements (51% vs. 20%, p  = 0.002) but few differences in symptoms when compared to patients with moderate thrombocytopenia. These results suggest that MF patients with thrombocytopenia experience greater symptomatic burden than MF patients without thrombocytopenia and may benefit from additional therapies.